MUSIC AND THEATRE ART OF THE UKRAINIAN DIASPORA: PRESERVING THE TRADITIONS OF LES KURBAS AND INNOVATIONS - Karas`, Hanna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Purpose: The development of Ukrainian music-dramatic theatre art in the diaspora throughout the 20th century and up to the present day is considered. The preservation of the traditions of the «Young Theatre» and the «Berezil» Art Assocciation of the outstanding Ukrainian director, theatre theoretician, playwright Les Kurbas by his students and followers Yosyp Hirnyak, Olimpia Dobrovolska and Volodymyr Blavatsky in the conditions of DP camps in Europe, later, after the end of the Second World War, was followed, – in the USA and Canada. Attention is drawn to opera, operetta, music-dramatic genres, as well as melodeclamation. The artistic group «Yara» («Yara Arts Group») under the leadership of Virlana Tkach, which operates at the experimental theatre «LA MAMA» in New York, is considered as a transformation of Kurbas traditions in the modern cultural space of the diaspora. Research methodology. The key research method is descriptive. At the same time, the method of comparison was used to clarify the peculiarities of the theatrical process in Ukraine and the diaspora. For the reconstruction of this picture, the memoirs of Volodymyr Blavatskyi by Yosyp Hirniak, scientific researches of diaspora theatre experts H. Luzhnytski, B. Boychuk, V. Revutski, Ukrainian art critic V. Haydabury, materials of memorial collections about the camps Mittenwald, Regensburg, “Our Theatre” and others were used. The results. The multi-genre music and theatre art of the Ukrainian diaspora and the multi-vector presentation of Ukrainian musical culture in the performances of the experimental theatre «LA MAMA» and «YARA ARTS GROUP» from New York demonstrate the durability of traditions from the modern theatre of Les Kurbas “Berezil” on the one hand, and the search for new means expressiveness in the conditions of the XXI century, on the other hand, because avant-garde theatre artists are constantly trying to invent something new, why there are no analogues in any corner of the world.